Brussels Newspeak or Populist Rhetoric? - Eftimova, Andreana (Media and Language, 2017)
Media speech reflects most vividly problems in the functioning of language and ongoing processes in speech practice. That is why in its mirror often we examine the speech of politicians which is in direct relation to the main trends in speech practice – intellectualization and democratization of speech. To designate two styles political discourse, the article introduces two terminological phrases – Brussels newspeak and populist rhetoric. It outputs main linguistic characteristics of these styles.